Detection of nitrite degradation by Lactobacillus plantarum DMDL9010 through the anaerobic respiration electron transport chain using proteomic analysis. (24th November 2020) - Yao, Kun; Liu, Dong‐mei; Liang, Ming‐hua; Brennan, Charles S.; Brennan, Margaret
Abstract: This study aimed to investigate the mechanism of nitrite degradation by Lactobacillus plantarum DMDL9010 using the proteomic technology. The results showed that 0.276 g L −1 nitrite was degraded completely by L. plantarum DMDL9010 in 24 h. Nitrite was transported into the pericytoplasm by a two‐component system. Reduced nicotinamide adenine dinucleotide (NADH) and flavin adenine dinucleotide‐2 (FADH2 ) were produced during metabolism via these pathways of phosphotransferase system, glycolysis/gluconeogenesis and citrate cycle. NADH and FADH2 produced electrons catalysed by dehydrogenase. The electrons were transferred through the electron transport chain eventually to nitrite. Some molecules of nitrites gained electrons and were reduced to NH3 by nitrite reductase. Then NH3 from nitrite was converted into l ‐glutamine catalysed by glutamine synthetase, which was one of the ways to generate l ‐glutamine. This study can provide theoretical guidance to the research on the biological technique to reduce nitrite in food products. Abstract : The mechanism of nitrite degradation was investigated by Lactobacillus plantarum DMDL9010 using the proteomic technology. Nitrite was transported into the pericytoplasm by a two‐component system. Some molecules of nitrites gained electrons and were reduced to NH3 by nitrite reductase. Then NH3 from nitrite was converted into L‐glutamine catalyzed by glutamine synthetase, which was one of the ways to generate Lglutamine.